The determinant factors of financial management behaviour during financial crisis in Klang Valley - Adi Nuraishah, Mohd Radzi (2022)
Financial behaviour has a significant impact on the well-being of individuals in a home, society, nation, and the globe at large. According to economic literature, every individual will analyse all available information in order to make decisions that maximise utility, profit, and wellbeing. The primary objective of this study is to examine the determinants factors of financial behaviour management of working adults. It is commonly considered that all people have an infinite ability to comprehend information in order to make educated decisions. The working adults in Malaysia were tested for their personal financial management knowledge, attitude, and behaviour. Financial management trends, strengths, and weaknesses were also discovered. Questionnaire were randomly distributed among working adults in Klang Valley, Malaysia in 2022 and 350 sample were chosen. Additionally, this study used a variety of research designs, including regression analysis utilising one-way ANOVA, independent samples t-test, descriptive analysis, and correlation analysis. The results of this study demonstrate that financial attitude and knowledge are major predictors of financial management behaviour among working people in Malaysia, particularly in the Klang Valley area. This paper provides the framework for further investigation and highlights the urgent need for a financial education programme to assist working adults in making wise financial decisions. As for that, this study has been acknowledged and proposed several strategies in this study to improve financial management behaviour.